Moisture sorption characteristics of bandi from San Joaquin, Iloilo. - Waldato, Marie Dame Earl Estrosas
The study determined the moisture sorption characteristics of bandi obtained from a specific store in Brgy. Qui-anan, San Joaquin Iloilo through static gravimetric method. The physichochemical properties such as water activity and moisture content, and microbiological property specifically the yeast and mold count were assessed before and after the 14-day storage under 30°C, 40°C and 50°C storage temperatures. Result of the experiment showed that there is significant difference between the initial and final water activity values stored under the three storage temperatures. Results, however, showed no significant difference on the initial and final moisture content of the sample stored under the 40°C and 50°C while a significant difference on the sample under the 30°C storage was determined. The moisture sorption isotherm of bandi was determined at three storage temperatures over the relative humidity range of 11.28% to 92.31%. Isotherm curves showed that bandi possesses a type III (J-shaped) isotherm. Three models were used to fit the experimental sorption data namely the Brunauer-Emmett-Teller (BET), Guggenheim-Anderson-de Boer (GAB) and Henderson. Standard Error of Estimation was used to evaluate the goodness of fit of the mathematical models. Among the three, the GAB model was found to be the most suitable for the description of the sorption data at three temperatures with monolayer moisture contents (m0) ranging from 5.94% to 8.95%. From the generated moisture sorption isotherm, it can be concluded that bandi should be stored at 40°C with relative humidity not exceeding 75%. For 30°C, relative humidity should not be beyond 40°C and 50°C storage temperature should have a relative humidity not greater than 75%.